National Volunteer Service: A Conceptual Model of Sustainable National Reform (European journal of volunteering and community-based projects, 2024)
Purpose. Bangladesh is currently experiencing a rejuvenation as a true democratic nation, following a nationwide movement where students played a pivotal role in liberating the country from a decade-long autocratic regime. Students are now actively participating in emergency public service management, including rescue and relief efforts, traffic control, public security, advocacy, and sanitation. This study proposes a conceptual model that could serve as an effective intervention to sustain the momentum of these national reforms, organizing student volunteer participation in a permanent and structured manner for national development and crisis management. Harnessing this substantial demographic dividend and social capital, a National Volunteer Service (NVS) could be a strategic imperative for Bangladesh's development.Design. The aim of this study is to explore the necessity of such a program or organization to propose guidelines for its implementation. The study is qualitative, drawing on interviews with key stakeholders who have field-level experience as volunteers and are involved in volunteer organizations and public service.Findings. The findings highlight the critical need for student engagement in national service, identify potential areas for involvement, and address possible challenges.Value. The study underscores the urgent need to initiate a National Volunteer Service and offers preliminary guidelines for its establishment.
Keywords: National Reform Movement, Youth Development, Volunteerism, Volunteer Service, Volunteer Organization, Volunteer Administration.